2011
DOI: 10.1105/tpc.110.082867
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Gene Networks Regulating Arabidopsis Plant Metabolism in Response to Various Stresses and Nutritional Cues

Abstract: The expression pattern of any pair of genes may be negatively correlated, positively correlated, or not correlated at all in response to different stresses and even different progression stages of the stress. This makes it difficult to identify such relationships by classical statistical tools such as the Pearson correlation coefficient. Hence, dedicated bioinformatics approaches that are able to identify groups of cues in which there is a positive or negative expression correlation between pairs or groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
88
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 28 publications
7
88
0
1
Order By: Relevance
“…Previous studies have 99 shown that the saccharopine pathway of lysine catabolism may also be involved in a 100 stress-related metabolic pathway in both dicots and monocots. Yet, the metabolic linkage 101 and stress response between Arabidopsis and maize -differed (Galili et al, 2002;Moulin 102 et al 2000Moulin 102 et al , 2006Less et al 2011;Kiyota et al, 2015). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have 99 shown that the saccharopine pathway of lysine catabolism may also be involved in a 100 stress-related metabolic pathway in both dicots and monocots. Yet, the metabolic linkage 101 and stress response between Arabidopsis and maize -differed (Galili et al, 2002;Moulin 102 et al 2000Moulin 102 et al , 2006Less et al 2011;Kiyota et al, 2015). …”
mentioning
confidence: 99%
“…The metabolic connection of the aspartate family pathway with the tricarboxylic acid 90 (TCA) cycle has been mapped in Arabidopsis (Less et al, 2011;Galili et al, 2011). The 91 results from Galili's group have shown that enhancing lysine synthesis and inhibiting its 92 catabolism in Arabidopsis had a notable influence on the levels of several TCA cycle 93 metabolites (Angelovici et al, 2010(Angelovici et al, , 2009Galili, 2003, 2004;Galili and Amir, 94 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Further examples where these databases and/or methods have been used for candidate gene discovery encompass different processes such as starch metabolism, 16,17 seed germination 18 and shade avoidance. 19 However, many of these approaches rely primarily on simple Pearson correlation, sometimes coupled with network clustering approaches 20 or sequence analysis. 21,22 Recently, more elaborate methods than Pearson correlation have flourished in the biostatistical literature, with the aim of increasing the accuracy of expression-based gene association inference.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, different external cues may trigger a coordinated expression of different sets of genes, making it difficult to identify such expression coordination by classical tools such as Pearson correlation. In a recent report, 1 we described a dedicated bioinformatics approach that is able to elucidate specific cues (particularly abiotic and biotic stresses) in which the change in expression of specific sets of genes is either positively coordinated (genes are either co-induced or co-suppressed) or negatively coordinated (one set is induced and the second set is suppressed). Our study analyzed the entire collections of Arabidopsis thaliana genes predicted to encode transcription factors (TFs) and metabolic enzymes (see details in reference 1), and two steps were used: (1) assembly of genes into cliques showing co-expression in a number of cues that is higher than a random background; and (2) clustering of the cliques.…”
mentioning
confidence: 99%